Overexpression of the ∆Np73 isoform is associated with centrosome amplification in brain tumor cell lines - Mikulenkova, Erika; Neradil, Jakub; Zitterbart, Karel; Sterba, Jaroslav; Veselska, Renata (Tumour biology, 2015)
The p73 protein is a member of the p53 family, and this protein is known to be essential for the maintenance of genomic stability, DNA repair, and apoptosis regulation. Transcription from two promoters leads to two main N-terminal isoforms: the TAp73 isoform is reported to have tumor suppressor function, whereas the ΔNp73 isoform likely has oncogenic potential. The present study is focused on the investigation of a possible role of both these p73 N-terminal isoforms in the process of centrosome amplification. HGG-02 and GM7 glioblastoma cell lines and the Daoy medulloblastoma cell line were used in this study. The cells were analyzed using indirect immunofluorescence to determine TAp73 and ΔNp73 expression patterns and possible co-localization with the BubR1 protein, as well as the number of centrosomes. A transiently transfected GM7 cell line was used to verify the results concerning the N-terminal isoforms in relation to centrosome amplification. We found that increased immunoreactivity for the ΔNp73 isoform is associated with the occurrence of an abnormal number of centrosomes in particular cells. Using the transiently transfected GM7 cell line, we confirmed that centrosome amplification is present in cells with overexpression of the ΔNp73 isoform. In contrast, the immunoreactivity for the TAp73 isoform was weak or medium in most of the cells with an aberrant number of centrosomes. To determine the putative counterpart of the p73 N-terminal isoforms among spindle assembly checkpoint (SAC) proteins, we also evaluated possible interactions between the N-terminal isoforms and BubR1 protein, but no co-localization of these proteins was observed.
Keywords: fluorescenční protilátková technika nepřímá; Protein Isoforms; Glioblastoma multiforme; Brain Neoplasms; protein-serin-threoninkinasy; protein p73; nádory mozku; Protein Serine-Threonine Kinases; chromozomální aberace; Tumor Suppressor Proteins; centrozom; jaderné proteiny; promotorové oblasti (genetika); DNA vazebné proteiny; Fluorescent Antibody Technique, Indirect; protein - isoformy; Gene Amplification; BubR1; TAp73; nádorové supresorové proteiny; amplifikace genu; DNA Repair; oprava DNA; Chromosome Aberrations; lidé; Humans; ΔNp73; Centrosome amplification; Promoter Regions, Genetic; Tumor Protein p73; nádorové buňky kultivované; Tumor Cells, Cultured; Nuclear Proteins; DNA-Binding Proteins; Centrosome; Medulloblastoma